DIGITAL SAVVY: BUILDING DIGITAL INTELLIGENCE IN 21ST CENTURY EDUCATION - Loso Judijanto; Farida Asy'ari; Iwan Setiawan; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The development of digital intelligence in education is an area that continues to receive academic and practical attention amid rapid technological advances. This research aims to analyze and synthesize the results of recent studies on digital intelligence implementation strategies in the school environment and the challenges faced. By using the literature research method in accordance with the theory of the research context. The results show that unequal access to technological resources, deficiencies in educator training on educational technology, and disparities in digital skills among teachers are the main challenges in integrating digital intelligence in schools. Our findings also emphasize the need for strong technology infrastructure development, comprehensive teacher training programs, and collaborative learning initiatives among teachers to overcome these barriers.